PENGUATAN PENGELOLAAN EKOSISTEM GAMBUT BERKELANJUTAN BERBASIS MASYARAKAT DI KABUPATEN NAGAN RAYA PROVINSI ACEH - Pribadyo; Astiah Amir; Meylis Safriani; Agustiar; Mukrami (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
The peatland ecosystem in Nagan Raya Regency is under significant pressure due to the construction of artificial canals, land-use conversion, and unsustainable cultivation practices, which have increased vulnerability to fires and degraded environmental quality. In this context, the SUPA-GIZ project implemented a community service initiative aimed at supporting peatland ecosystem restoration through a participatory approach. The approach involved cross-stakeholder coordination, including local government authorities, farmer groups, and community organizations, to ensure the engagement of all relevant parties. The activities employed methods such as field surveys to identify critical canals contributing to degradation, awareness campaigns on the importance of peatland conservation, technical training on canal blocking, and the development of restoration intervention designs. The results of these activities demonstrated significant achievements, including the identification of ten critical canals requiring immediate attention, an increase in community understanding of the peatland ecosystem from 35% to 82%, and the establishment of Village Peatland Alert Teams. Changes in community behavior, such as implementing canal-blocking techniques and practicing more environmentally friendly land management, served as indicators of the intervention’s success. This participatory model demonstrated the effectiveness of combining local education with technical interventions to mitigate peat fire risks. The success of this approach presents opportunities for replicating community-based strategies in other peatland areas, offering a sustainable method for ecosystem restoration, fire risk reduction, and the enhancement of community capacity for collective environmental management.